Prionové proteiny a jejich interakce s těžkými kovy - Sedláčková, Eliška; Cardová, Alžběta; Adam, Vojtěch; Kizek, René (Journal of Metallomics and Nanotechnologies, 2014)
In this study we attempted to characterize cellular prion-like protein (PrPC) properties and its possible interactions with metal ions. In the first part of this study we described the structure of prion-like protein, its biochemical properties and its role in human or animal organism. In the next and the most important part we summarized accessible information about the metals and heavy metals which can bind prion-like protein. Especially the heavy metals could have really important role in the process of protein misfolding, but this role is still unknown. In the last section we focused on transmissible spongiform encephalopathies, their incubation period and clinical signs.
Keywords: Animals; Prion Diseases; kadmium; Cadmium; Metals; lidé; PrPC proteiny; kovy; měď; PrPC Proteins; Copper; PrPSc proteiny; PrPSc Proteins; Prions; těžké kovy; prionové nemoci; priony; zvířata; Metals, Heavy; Humans